Virtual power plants: challenges, opportunities and advantages in modern national and international energy markets - N. G. Lyubimova; A. S. Flaksman; D. A. Pankov (Вестник университета, 2025)
An innovative trend in the energy sector such as virtual power plants (hereinafter referred to as VPPs) opens new horizons for modernization of the industry. This technology not only meets modern requirements for flexibility and sustainability of power systems, but also contributes to their more efficient integration. By consolidating distributed energy resources, VPPs contribute to grid reliability and economic efficiency. Despite the obvious advantages, VPPs integration into existing energy markets is fraught with serious obstacles. The key issue remains in the lack of an adequate regulatory framework that can consider the specific features of these innovative systems. This fact dictates an urgent need for developing innovative approaches to VPPs regulation. The study aims to identify and examine in detail the potential application of VPPs in modern energy sites. The methodological basis is a comprehensive STEEP analysis covering social, technological, environmental, economic, and political aspects of virtual power plants. This toolkit allows for a comprehensive assessment of both the challenges and potential benefits of implementing VPPs. The need to create a favorable environment for VPPs development through forming appropriate political and regulatory infrastructure has been established. Only a comprehensive approach, considering all aspects of STEEP analysis, can ensure full realization of virtual power plants potential in modern energy sector.